The lumbar spine age-related degenerative disease influences the BMD not the TBS: the Osteolaus cohort. Issue 3 (March 2017) - Padlina, I.; Gonzalez-Rodriguez, E.; Hans, D.; Metzger, M.; Stoll, D.; Aubry-Rozier, B.; Lamy, O.
Abstract Summary We evaluated the influence of degenerative disease and fractured vertebra on lumbar spine bone mineral density (BMD) and trabecular bone score (TBS) in 1500 women aged 50–80 years. TBS was not affected by a degenerative disease. While BMD increases after 62.5 years, TBS continues to decline. TBS should play a leading role in lumbar spine evaluation. Introduction After menopause, lumbar spine (LS) BMD and TBS values decrease. Degenerative disease (DD) increases with age and affect LS BMD. The aim of this study was to measure changes in LS BMD and TBS in women 50 to 80 years old, taking into account the impact of fractured vertebrae and DD. Methods LS BMD, TBS, and vertebral fracture assessment were evaluated in the OsteoLaus cohort (1500 women, 50–80 years old). The exams were analyzed following ISCD guidelines to identify vertebrae with fractures or DD (Vex). Results 1443 women were enrolled: mean age 66.7 ± 11.7 years, BMI 25.7 ± 4.4. LS BMD and TBS were weakly correlated (r2 = 0.16). The correlation (Vex excluded) between age and BMD was +0.03, between age and TBS −0.34. According to age group, LS BMD was 1.2 to 3.2% higher before excluding Vex (p < 0.001). TBS had an insignificant change of <1% after excluding Vex. LS BMD (Vex) decreased by 4.6% between 52.5 and 62.5 years, and increased by 2.6% between 62.5 and 77.5 years. TBS (Vex excluded) values decreased steadily with age with an overall loss of 8.99% between 52.5 and 77.5 years. Spine TBS, femoral neck, and total hip BMD gradually decreased with age, reaching one SD between the oldest and youngest group. Conclusions TBS is not affected by DD. While BMD increases after 62.5 years, TBS continues to decline. For lumbar spine evaluation, in view of its independence from DD, TBS should play a leading role in the diagnosis in complement to BMD.